2021
DOI: 10.3329/cmoshmcj.v20i2.56465
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Adverse Drug Reaction Reporting by the Physicians in A Medical College Hospital

Abstract: Background: In order to improve the spontaneous Adverse Drug Reaction (ADR) reporting practice by the physicians, there is an obligatory need to investigate the current situation of ADR reporting by them. The study was conducted to observe the ADR reporting pattern among physicians in a tertiary medical college hospital. Materials and methods: This was a descriptive cross sectional study carried out in a tertiary medical college hospital during the study period of March 2020 to October 2020. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Noel, Sushma, and Guido (2004) [22] reported that, in a prospective hospital-based study, 32% of the cADRs were due to chemotherapeutic agents like ABs [22]. ADRs involving skin is also common in developing countries like-Bangladesh, India [11,20,[23][24][25][26]. A study conducted in the outpatient department of Dhaka Medical College Hospital, Bangladesh found that about 43% of ADRs were caused by ABs, and Skin and Appendages was the second most affected system (32%) next to the GIT (56%) [23].…”
Section: Background and Introductionmentioning
confidence: 99%
“…Noel, Sushma, and Guido (2004) [22] reported that, in a prospective hospital-based study, 32% of the cADRs were due to chemotherapeutic agents like ABs [22]. ADRs involving skin is also common in developing countries like-Bangladesh, India [11,20,[23][24][25][26]. A study conducted in the outpatient department of Dhaka Medical College Hospital, Bangladesh found that about 43% of ADRs were caused by ABs, and Skin and Appendages was the second most affected system (32%) next to the GIT (56%) [23].…”
Section: Background and Introductionmentioning
confidence: 99%
“…9 The current status of the physicians about ADR reporting has been evaluated in many studies so far showing lack of knowledge and practice. 10,11 In countries like Bangladesh with high population density, limited resources and fragmented health-care system, doctors remain substantially occupied in treatment and patient care. Besides, the ADR reporting has not yet been established as an obligatory task in our medical practice despite its presence on paper.…”
Section: Introductionmentioning
confidence: 99%